Quantification technique for analysing juvenile sacral trabecular microarchitecture: a micro-CT scan and Skyscan Ctanalyser method. - Yusof, Nurul Asyiqin; Soames, Roger W.; Black, Sue M.; Craig, Cunningham A. (2019)
Background/Objective: The study of trabecular bone provides information relating to bone strength. A number of imaging modalities are used to investigate the internal trabecular structure of human bone, including x-ray macroradiography, high resolution-CT (HRCT) and micro-computed tomography (micro-CT), with many studies focusing on adult bone analysis, including fracture management and osteoporosis-related bone density. However, only a limited number have investigated trabecular microarchitecture in juvenile bone.